LITERASI KEUANGAN DAN PERENCANAAN KEUANGAN PADA DANA PENDIDIKAN ANAK - Rita, Maria Rio; Santoso, Benny (Jurnal Ekonomi, 2015)
The purpose of this study is to analyze financial literacy and financial planning on educational funds for children among housewives. The participants of this study are 100 housewives in Sidorejo Lor, Salatiga. Data collection technique is using distribution questionnaires and conducting interviews to obtain more in-depth information. The collected data was analyzed using statistic descriptive analysis approach to investigate the level of financial literacy and financial planning on the children educational funds. Based on the results of the analysis, it can be concluded that: 1) Level of financial literacy on planning children educational funds among housewives in Sidorejo Lor Salatiga is categorized high level; 2) The financial planning on the education of children among housewives in Sidorejo Lor, Salatiga is categorized high.